Distribución de los grupos sanguíneos en indios guatusos de Costa Rica - Fuentes, Luis G. (1961)
Findings are reported on the blood groups of systems ABO, MN, Rh-Hr, Kell and Duffy, in 65 full blood and 8 halfbreed Guatuso indians from northern Costa Rica.Type O was found in all the full blood and in 75 per cent óf the half breed individuals. A and B ocurring in equal proportions among the latter. M factor was more frequent than N, although N was rather high (19.13%). ll cases were Rh- positive; cDE (R2) was more abundant than CDe (R1), which is assumed with reservations, to indicate racial purity. Low percentages of cDe (Ro) and CDE (Rz) are also reported. Kell factor was completely absent and Fy (a+) predominated in the Duffy system. The value of blood groups in anthropology is briefly discussed.